PELAKSANAAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) ANGKATAN 2 DI SMK NEGERI 5 PALANGKA RAYA TAHUN 2025 - Taufiqur Rahman, Eka; Anisa; Tesario Grunadi, Devin; Yohanes Batara, Wili; Rahayu, Mannisa; B. Tambun, Vinshenko; Benarrivo Gultom, Gerald; Lestari, Widya; Rahmawati, Maura; Eva Ngelista, Marcelena; Ratnaningtyas, Sambarani; Sukmawatie, Neny; Mauri, Lulu (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Education is a conscious effort to realize a cultural inheritance from one generation to another. Education is realized with a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and skills needed by themselves and society. In a simple and general sense, the meaning of education is a human effort to grow and develop innate potentials both physically and spiritually in accordance with the values that exist in society and culture. In order to prepare students to face social changes, culture, the world of work and rapid technological advances, student competencies must be prepared to be more commensurate with the needs of the times. Link and match is not only with the industrial world and the world of work but also with a rapidly changing future. Higher Education is required to be able to design and implement an innovative learning process so that students can achieve learning outcomes covering aspects of attitude, knowledge, and skills optimally and always relevant. The Merdeka Learning Policy - Merdeka Campus is expected to be the answer to these demands. The Merdeka Campus is a form of learning in universities that is autonomous and flexible so as to create a learning culture that is innovative, non-restrictive, and in accordance with the needs of students.